From nucleobase to DNA templates for precision supramolecular assemblies and synthetic polymers. Issue 25 (27th May 2016) - Surin, Mathieu
Abstract : In this minireview, we report on the recent advances of utilization of nucleobases and DNA as templates to achieve well-defined supramolecular polymers, synthetic polymers, and sequence-controlled polymers. Abstract : Owing to the great advances in the automated synthesis and programmed self-assembly of nucleic acids, these are readily used for advances in nanoscience, polymer science, supramolecular chemistry, and for elaborating complex chemical systems connected with the origin of life. In this minireview, we report on the recent advances of the utilization of nucleobases, nucleotides, and nucleic acids as templates to achieve well-defined supramolecular polymers, synthetic polymers, and sequence-controlled polymers. We particularly emphasize the aspects of supramolecular organization, self-assembly, chirality effects, and information transfer, going from nucleobase templating to DNA-templated polymerizations. Some recent developments of supramolecular hybrids involving nucleic acids are underlined for prospective biological applications.